Microencapsulação de probióticos por multicamadas para aplicação em alimentos - Menezes, Maria Fernanda da Silveira Cáceres de (2019)
The aim of this study was to evaluate the effects of microencapsulation promoted on the viability of free and microencapsulated Lactobacillus acidophilus by ionic gelation associated with electrostatic interaction from pectin particles and whey protein concentrate sequentially adsorbed in up to 3 layers. The particle production stage by ion gelation was performed with low esterification pectin, being gelified in the presence of calcium ions, followed by coating, by electrostatic interaction, with the protein concentrate. The probiotic used in the free and microencapsulated form was Lactobacillus acidhophilus LA 02. Four types of particles were made, one particle produced only with the encapsulant matrix, pectin (2%), which was considered a control, since it did not have any coating, was identified by LA/P0; LA/P1 was formed by pectin (2%) and a WPC coating (2%); LA/P2 was formed by pectin (2%), a WPC coating (2%) and pectin overlay (0.3%) and LA/P3 was formed by pectin (2%), a WPC coating (2%), pectin overlay (0.3%) and lastly again the WPC (0.5%), characterizing them as multilayer particles and the standard, the free microorganisms. The encapsulation efficiency, size and morphology were evaluated in order to characterize the wet and freeze dried particles, as well as the viability of free and microencapsulated lactobacilli after in vitro exposure to gastrointestinal conditions, after simulation of heat treatments and during 120 days of storage at freezing (-18ºC), refrigeration (5ºC) and ambient (25ºC) temperatures. Encapsulation efficiency decreased when layers were adsorbed to both wet and freeze dried particles. Regarding the size, WPC adsorption reduced the particle size ranging from 447.6 - 208.0 μm for wet and between 575.2 - 421.1 μm for freeze drieds. The particles were slightly spherical, however, the freeze dried process promoted structure rupture with superficial pores. Exposure to different pHs that simulate passage through the gastrointestinal tract showed that LA/P1 and LA/P3 wet microparticles showed low permeability under acidic conditions and high permeability to the neutral environment of the intestine, while free microorganisms showed loss of viability. These same particles, and freeze dried LA/P2, exhibited better resistance than free probiotics in the simulated intestinal fluid. Regarding the heat treatments applied to the wet particles, it was observed that the LA/P1 resisted the exposure at 63ºC for 30 min, since it did not present significant difference (p> 0.05) in relation to the initial count (9.57 log CFU/g). When subjected to 72ºC for 15s, LA/P1 was also more resistant, with a reduction of 2.14 log CFU / g, while free culture reduced 5.4 log CFU/g. The freeze-dried particles at 72ºC for 15s showed resistance to the test, except for LA/P0 and free lactobacilli that showed loss of viability. The best viability of the wet particles was obtained at a storage temperature of -18ºC, with counts of 7.86 log CFU/g for LA/P1 at the end of the period (120 days) and 6.55 log CFU/g for the storage. LA/P3 for 105 days. The freeze-dried particles LA/ P1, LA/P2 and LA/P3 presented satisfactory resistance to 120 days with viability of around 7 log CFU/g when stored at refrigeration (5°C) and freezing (-18°C). This study showed that external ionic gelation and electrostatic interaction using WPC associated multilayer pectin proved to be an effective microencapsulation system to promote greater protection and viability of Lactobacillus acidophilus against adverse conditions.